The Art of Happiness: An Explorative Study of a Contemplative Program for Subjective Well-Being - Rastelli, Clara; Calabrese, Lucia; Miller, Constance; Raffone, Antonino; De Pisapia, Nicola (Frontiers in Psychology, 2021)
In recent decades, psychological research on the effects of mindfulness-based interventions has greatly developed and demonstrated a range of beneficial outcomes in a variety of populations and contexts. Yet the question of how to foster subjective well-being and happiness remains open. Here, we assessed the effectiveness of an integrated mental training program “The Art of Happiness” on psychological well-being in a general population. The mental training program was designed to help practitioners develop new ways to nurture their own happiness, by cultivating their openness to others together with their own emotional and interpersonal well-being, by emphasizing both formal meditation and informal practices, reflections, as well as insights from contemplative wisdom traditions, with particular reference to Mahayana Buddhism philosophy, and from cognitive and affective neurosciences. The program included seven modules and was conducted over a period of nine months, also comprising two retreats, one in the middle and one at the end of the course. By using a set of established psychometric tools, we assessed the effects of such a mental training program on several psychological well-being dimensions, taking into account both the long-term effects of the course and the short-term effects arising from intensive retreat experiences. The results showed that several psychological well-being measures, especially life satisfaction, self-awareness, and emotional regulation, gradually increased as the participants progressed from the beginning to the end of the course, results evident in both long-term and short-term effects. These findings show the potential of the mental training program, such as “The Art of Happiness”, for psychological well-being.